Lectin microarray and mass spectrometric analysis of hepatitis C proteins reveals N-linked glycosylation. Issue 15 (April 2018) - Guo, Yonghong; Yu, Hanjie; Zhong, Yaogang; He, Yu; Qin, Xinmin; Qin, Yuan; Zhou, Yun; Zhang, Peixin; Zhang, Ying; Li, Zheng; Jia, Zhansheng
Abstract : Abstract: We used lectin microarray and mass spectrometric analysis to identify the N-linked glycosylation patterns of hepatitis C virus (HCV) particles. HCV J6/JFH-1 chimeric cell culture (HCVcc) in the culture supernatant was concentrated and purified by ultrafiltration and sucrose gradient ultracentrifugation. Twelve fractions were collected from the top and analyzed for viral infectivity and HCV RNA content after sucrose gradient separation. HCV RNA and proteins were separated by ultracentrifugation in a continuous 10% to 60% sucrose gradient to purify viral particles based on their sedimentation velocities. HCVcc particles were found mainly in fractions 6 to 8, as determined by quantitative polymerase chain reaction (qPCR) analysis for HCV RNA and ELISA of the HCV core protein. The N-glycans on HCV proteins were analyzed by lectin microarray and mass spectrometry. We identified that 32 of 37 lectins displayed the positive binding signals and 16 types of N-glycoforms of which the major HCV glycoforms were high mannose-type N-linked oligosaccharides, hybrid N-glycans, and fucosylated N-glycans. Our study provided new detailed information regarding the majority of the glycan–protein profile, complementing to previous findings of glycan–HCV protein interactions. Abstract : Supplemental Digital Content is available in the text